Metallurgical failure analysis of a steam trap bypass tube - Mohd Arif Anuar, Mohd Salleh; Darwin, Sebayang; Syahril, D. I. C; Anton, Sitompul (SIRIM, 2011)
4th Malaysian Powder Metallurgy Symposium (MPMS) and Malaysian Metallurgical Conference (MMC) 2010 organized by SIRIM Berhad on 22nd - 23rd November 2010 at Parkroyal Hotel, Penang, Malaysia.